Molecular Analysis of a Genetic Variants Panel Related to Nutrients and Metabolism: Association with Susceptibility to Gestational Diabetes and Cardiometabolic Risk in Affected Women - Marica Franzago; Federica Fraticelli; Antonio Nicolucci; Claudio Celentano; Marco Liberati; Liborio Stuppia; Ester Vitacolonna (Journal of Diabetes Research)
Gestational diabetes mellitus (GDM) is the most frequent metabolic disorder in pregnancy. Women with a GDM history are at increased risk of developing diabetes and cardiovascular diseases. Studies have demonstrated a significant correlation between several genes involved in the metabolic pathway of insulin and environmental factors. The aim of this study was to investigate the relationship between clinical parameters in GDM and variants in genes involved with nutrients and metabolism. Several variants PPARG2 rs1801282 (C>G); PPARGC1A rs8192678 (C>T); TCF7L2 rs7903146 (C>T); LDLR rs2228671 (C>T); MTHFR rs1801133 (C>T); APOA5 rs662799 (T>C); GCKR rs1260326 (C>T); FTO rs9939609 (T>A); MC4R rs17782313 (T>C) were genotyped in 168 pregnant Caucasian women with or without GDM by High Resolution Melting (HRM) analysis. A significant correlation was observed between TT genotype of TCF7L2 gene and increased risk of GDM (OR 5.4 [95% CI 1.5–19.3]). Moreover, a significant correlation was observed between lipid parameters and genetic variations in additional genes, namely, PPARG2 [p = 0,02], APOA5 [p = 0,02], MC4R [p = 0,03], LDLR [p = 0,01], and FTO [p = 0,02]. Our findings support the association between TCF7L2 rs7903146 variant and an increased GDM risk. Results about the investigated genetic variants provide important information about cardiometabolic risk in GDM and help to plan future prevention studies.